Social justice in Vietnam: Perspective and practice (Revista de Investigaciones Universidad del Quindío, 2023)
The issue of social justice is a fundamental issue of each era and has a great topical significance because it is posed together with human existence, associated with dreams and aspirations towards a nice and happy life. After all, the goal of economic growth is to serve people, the subject of development, fairly and progressively. Because, "Humans, ultimately mastering their social existence, are also thereby mastering nature, mastering themselves, and becoming free man" (Marx & Engels, 1995, p.333). It is further confirmed in the United Nations Human Development Report (1995) when it says: “what does development mean without regard to human life?”. The purpose of economic development, after all, is only a means to serve human development. It is people who create conditions, seize opportunities, and turn them into a driving force to realize their development goals, which in turn will promote socio-economic development. In the process of international integration, Vietnam has actively implemented policies to achieve social justice and has achieved certain results, contributing to improving the living standards of all people. There are certain limitations that need to be addressed to realize social justice in all of social life. The article analyzes the viewpoints and practices of implementing social justice in Vietnam, thereby proposing solutions to effectively implement social justice in Vietnam today.
Keywords: social justice; social development; perspective; practice; Vietnam